2014
DOI: 10.1051/0004-6361/201323178
|View full text |Cite
|
Sign up to set email alerts
|

Dust reverberation-mapping of the Seyfert 1 galaxy WPVS48

Abstract: Using robotic telescopes of the Universitätssternwarte Bochum near Cerro Armazones in Chile, we monitored the z = 0.0377 Seyfert-1 galaxy WPVS48 (2MASX J09594263-3112581) in the optical (B and R) and near-infrared (NIR, J and K s ) with a cadence of two days. The light curves show unprecedented variability details. The NIR variation features of WPVS48 are consistent with the corresponding optical variations, but the features appear sharper in the NIR than in the optical, suggesting that the optical photons und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…The BLR reverberation mapping observations for local Seyfert galaxies and some high redshift quasars have been carried out by several groups (e.g., Peterson et al 1998Peterson et al , 2004Kaspi et al 2000;Bentz et al 2009b;Denney et al 2010;Grier et al 2012;Du et al 2014;Fausnaugh et al 2017); a compilation of ∼ 40 AGNs with secure Hβ BLR lag detection can be found in Bentz & Katz (2015) (see also Bentz et al 2009aBentz et al , 2013. Dust reverberation mapping observations have also been measured for several AGNs (Clavel et al 1989;Glass 1992;Sitko et al 1993;Glass 2004;Suganuma et al 2006;Koshida et al 2014;Pozo Nuñez et al 2014Schnülle et al 2015;Lira et al 2015;Vazquez et al 2015;Mandal et al 2018;Ramolla et al 2018;Landt et al 2019). The first systematic investigation of dust reverberation mapping was carried out by the Multicolour Active Galactic Nuclei Monitoring (MAGNUM) project (Yoshii 2002;Yoshii et al 2003;Minezaki et al 2004;Tomita et al 2006;Suganuma et al 2006;Koshida et al 2009;Sakata et al 2010;Koshida et al 2014;Yoshii et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The BLR reverberation mapping observations for local Seyfert galaxies and some high redshift quasars have been carried out by several groups (e.g., Peterson et al 1998Peterson et al , 2004Kaspi et al 2000;Bentz et al 2009b;Denney et al 2010;Grier et al 2012;Du et al 2014;Fausnaugh et al 2017); a compilation of ∼ 40 AGNs with secure Hβ BLR lag detection can be found in Bentz & Katz (2015) (see also Bentz et al 2009aBentz et al , 2013. Dust reverberation mapping observations have also been measured for several AGNs (Clavel et al 1989;Glass 1992;Sitko et al 1993;Glass 2004;Suganuma et al 2006;Koshida et al 2014;Pozo Nuñez et al 2014Schnülle et al 2015;Lira et al 2015;Vazquez et al 2015;Mandal et al 2018;Ramolla et al 2018;Landt et al 2019). The first systematic investigation of dust reverberation mapping was carried out by the Multicolour Active Galactic Nuclei Monitoring (MAGNUM) project (Yoshii 2002;Yoshii et al 2003;Minezaki et al 2004;Tomita et al 2006;Suganuma et al 2006;Koshida et al 2009;Sakata et al 2010;Koshida et al 2014;Yoshii et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that a component of hot graphite dust residing within the ISM dust sublimation radius is required to account for a peak in the NIR SED of broad-line AGN (Mor & Netzer 2012; 10 42 10 43 10 44 10 2 10 1 10 0 r lag (pc) Rd,ISM,iso Rd,C,iso toriso 10 42 10 43 10 44 10 45 10 2 10 1 10 0 toraniso Suganuma et al 2006Clavel et al 1989Koshida et al 2014Pozo Nunez et al 2015& 2014Mandal et al 2018Lira et al 2011& 2015 L V (erg/s) Fig. 23.-The K-band radius-luminosity relationships for the observationally determined values of r K available in the literature (Clavel et al 1989;Suganuma et al 2006;Lira et al 2011;Koshida et al 2014;Pozo Nuñez et al 2014;Lira et al 2015;Pozo Nuñez et al 2015;Mandal et al 2018) and for r RW,K values derived from a subset of our globally optically thick torus models. The values of r RW corresponding to the median value of the RWD and the range between minimum and maximum RWD values at λ = 2.2 µm are represented by a solid line and a shaded band, respectively, for both the isotropically (blue; left panel) and anisotropically (red; right panel) illuminated torus.…”
Section: Rwd-lwr Relationship and Implications Formentioning
confidence: 99%
“…The dust reverberation radius has now been measured by NIR (K-band) reverberation mapping for about 20 AGN (e.g., Nelson 1996;Oknyanskij & Horne 2001;Minezaki et al 2004;Suganuma et al 2006;Lira et al 2011;Koshida et al 2014;Pozo Nuñez et al 2014;Lira et al 2015;Mandal et al 2018). Some of the authors of this paper are members of a collaboration that recently conducted a 2.5 year monitoring campaign, during which 12 broad-line AGN were observed using the Spitzer Space Telescope at 3.6 and 4.5 µm, supported by ground-based optical observations.…”
Section: Introductionmentioning
confidence: 99%
“…We collect K-band lags and absolute V-band magnitudes M obs V of 20 AGN from the literature (Lira et al 2011;Koshida et al 2014;Pozo Nuñez et al 2014. These are used as a comparison sample to our simulations.…”
Section: Appendix A: Comparison Of Simulated Lag-luminosity Relation mentioning
confidence: 99%